Evaluasi Kekuatan Struktur Atas Gedung SD Madiun Lor 3 Kota Madiun - Kholilur Rohman, Rosyid; Rochidajah, Rochidajah (JURNAL AGRI-TEK, 2015)
Madiun Lor 3 Elementary school building located at Yos Sudarso street in Madiun city. Early this building constructed one floor. Then to fulfil need of classroom planned this building 2 floor. In the process of construction there is doubt in strength of structure. This research focused to evaluation of slab, beam and column based on SNI 2847 2002. Hammer test was be done to slab, beam and column. Field observation result show quality of concrete fc’16 MPa. Steel quality assumed fy 240 MPa. Analysis result indicated that slab structure was strong enough, beam and column structure were strong enough either.Keyword : hammer test, slab, beam, column